THE EFFECT OF DIFFERENT SHADING LEVELS ON PRODUCTIVITY Asystasia gangetica (L.) subsp. Micrantha ON THE THIRD CUT - L.R. B., Sembiring; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2024)
This research aims to determine the effect of different levels of protection on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha on the third cut. This research lasted for three months and was carried out in the greenhouse of Sading Village, Mengwi District, Badung Regency. The design used was a completely randomized design (CRD) consisting of four treatments and each was repeated seven times, so there were 28 experimental units. The treatments are: N0: 0% shade (without paranet); N1: Shade 20% (1 layer of paranet); N2: Shade 40% (2 layers of paranet); and N3: 60% shade (3 layers of paranet). The variables observed are growth variables, yield variables, and plant growth characteristic variables. The results of the research show that different levels of shade have an effect on growth variables, yield variables and plant growth characteristic variables. It can be concluded that different levels of shade affect the growth and yield of Asystasia gangetica plants at the third cutting. A shade level of 20% (N1) provides the best growth and results for Asystasia gangetica (L.) subsp. Micrantha on the third cut.